Modern Recent on the Laboratory Diagnosis of Clostridium Difficile-associated Infection - A. S. Kvet naya,; P. S. Makridi; M. K. Behtereva (Журнал инфектологии)
In the review the current information on the laboratory diagnosis of Clostridium difficile-associated infection. Made a critical assessment of the effectiveness and specificity of the modern methods of diagnosis: methods of isolation and identification of Clostridium difficile cultures by studying the biochemical characteristics, the use of test kits – API 20A and Rapid Ana II-tests, determination of protein spectra by means of MALDI-TOF mass spectrometry. Describes how to display toxigenic strains of Clostridium difficile based on Dot-immunoblotting, PCR, and immunochromatography, as well as methods for determining the toxin Clostridium difficile in stool samples by determining the cytotoxic effect of toxins on tissue culture, latex agglutination test, ELISA and enzyme-linked fluorescent assay.